Relationship between parental psychological control and suicide ideation in Chinese adolescents: Chained mediation through resilience and maladjustment problems - Sun, Ji; Ban, Yongfei (Frontiers in Psychology, 2022)
Suicide ideation is an essential predictor of suicide deaths and is highly prevalent among Chinese adolescents. Several studies have highlighted the significant association between parental psychological control and suicide ideation. However, few studies have focused on the potential mechanisms underlying this relationship. This study investigated the chained mediating effects of resilience and maladjustment problems on the relationship between parental psychological control and suicide ideation among Chinese adolescents. A total of 2,042 students in junior high school completed measurements. The results revealed significant correlations among parental psychological control, resilience, maladjustment problems and suicide ideation. Even after controlling for the effects of gender and grade, parental psychological control positively predicted a significant effect of suicide ideation. Furthermore, suicide ideation was linked with parental psychological control through three pathways: the mediating role of resilience, the mediating role of maladjustment problems, and the chained mediating role of resilience and maladjustment problems. These findings have broad implications for the field of suicide studies. High levels of parental psychological control, low levels of resilience, and high levels of maladjustment problems may increase the occurrence of suicide ideation.